Intention to Use Credit Card among College Students in Greater Jakarta - Suresh Kumar; Lin Karlina (JAAF (Journal of Applied Accounting and Finance), 2020)
This study aims to determine the influence of the role of parents, financial knowledge, and customer's attitude towards credit card which are determinants of a person's intention to using a credit card. This study applied quantitative data analysis and used an online survey platform as a medium to distribute questionnaires consisting of 22 item statements. A total of 322 responses were collected with 302 valid responses with purposive sampling technique. Structural equation modelling was applied to test the hypothesis. The results of this study indicate that all hypotheses (parents’ role, financial knowledge, and attitude) toward intention to use credit card are accepted and the model is also very good where the coefficient of determination is close to one. This study provides a better understanding of customer intentions in determining the purchase decision using a credit card in Greater Jakarta area. This study also provides managerial implications for business and recommendations for future research.